Jews and the American Religious Landscape. - Rebhun, Uzi (Columbia University Press, 2016)
Jews and the American Religious Landscape explores major, complementary facets of American Judaism and Jewish life through a comprehensive analysis of contemporary demographic data. Focusing on the most important aspects of social developmentgeographic location, socioeconomic stratification, family dynamics, group identification, and political orientationthe volume adds empirical value to questions concerning the strengths of Jews as a religious and cultural group in America and the strategies they have developed to integrate successfully into a Christian society. Drawing heavily on findings.